Fuzzy Control Design for Energy Efficient Heat Exchanger Network - Anna Vasickaninová (AIDIC Servizi S.r.l., 2021)
Increasing energy efficiency and decreasing power consumption play a substantial role in the modern industrial and technological world. Consequently, there are enhanced requirements on all production processes and especially on energy intensive processes. Heat exchangers (HEs) and heat exchanger networks (HENs) are very energy intensive processes and only their optimal operation assures efficient heat recovery. Advanced optimization and advanced control are tools for assuring the energetic efficacy of HEs or HENs. Between them, fuzzy logic control represents the advanced control strategy that has many applications in industry and advantages as it can be used for control of strongly non-linear processes and processes that are difficult to control because of asymmetric dynamics or uncertainties. The type-1 and type-2 fuzzy logic controllers (FLCs) designed for a small heat exchanger network (HEN) are compared in this paper using simulation results with the PI and PID controllers tuned by conventional methods. The controlled HEN was a combination of two heat exchangers in series and one in parallel to them. The best controller was the type-2 fuzzy logic controller (FLC). This controller assured the most efficient operation of HEN measured by the smallest coolant consumption. The coolant consumption increased exploiting the type-1 FLC by 2 %, the PI controller by 3 %, and the PID controller by 5 %.